Static and dynamic impacts of MERCOSUR: The case of the pharmaceutical sector - Marta Bekerman; Pablo Sirlin (CEPAL Review, 2001)
This article analyses the impact of MERCOSUR on the pharmaceutical sector. It concludes, among other things, that the sector suffered strong impacts, both static and dynamic, as a result of the integration process. From the static point of view, it may be observed that integration has given rise to a marked increase in intrazonal trade, which reflects the existence of a substantial trade creation process in MERCOSUR. From the dynamic point of view, the outstanding aspect is the increasing interest in regaining a place in the markets of Argentina and Brazil shown by transnational corporations since the integration process. This process, together with the changes in the regulations on medical patents, has given rise to big changes in the strategies and positions of laboratories of domestic origin.